Management of Language Politeness Development in Improving Digital Literacy for High School Students - Panji Pratama; Sofyan Sauri; Waska Warta; Hendi Suhendraya Muchtar (CV. Inara, 2022)
In the digital era, especially Society 5.0, communication is the most important thing. Unfortunately, our students are not prepared to play a real role in such a social community. This is none other than weak digital literacy. This study aims to reveal and describe: (1) planning, (2) implementation, (3) evaluation, to foster language politeness in improving literacy. digital for high school students. This study uses a qualitative approach with a descriptive method. The theoretical basis used in this research is management theory and pragmatic theory. The main findings of this research are: (1) planning, through: setting goals and objectives; preparation of vision, mission, and strategy; preparation of programs and focus of activities; and implementation guidelines; (2) implementation, through: procurement and utilization of resources; technical instructions for learning Indonesian; Indonesian language learning model; application of reward and punishment in Indonesian language learning; (3) evaluation, through: learning model innovation; monitoring and supervision; and program feedback; In this study, the ADDICTIVE model was obtained as an alternative to learning management for the development of language politeness in improving digital literacy in high school students.